2009
DOI: 10.1194/jlr.p900033-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on factors associated with cardiovascular disease and the metabolic syndrome

Abstract: Supplementary key words twins • heritability • genetics • risk factorsCardiovascular disease (CVD) is the leading cause of death in the United States ( 1 ). Metabolic syndrome (MetS) is defi ned as the clustering of factors associated with elevated CVD risk including glucose intolerance, dyslipidaemia, hypertension, and central adiposity ( 2 ). Estimated to affect over 34% of American adults ( 1 ), MetS is designated as a secondary target of coronary heart disease risk-reduction therapy after the primary targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
96
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 68 publications
5
96
2
Order By: Relevance
“…These same risk factors account for over three quarters of ischemic heart disease. 2 These risk factors are influenced by both environmental exposures and genetic background and the heritability of these risk factors can be as high as 77%, 3 making it difficult to clearly separate CVD risk factors into genetic and nongenetic categories. The INTERHEART study has evaluated the effect of both physical and psychosocial factors on the risk of myocardial infarction and has shown that a higher prevalence of psychological stress and other psychosocial factors like depression account for 34% of the population attributable risk for myocardial infarction, independently of physical risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…These same risk factors account for over three quarters of ischemic heart disease. 2 These risk factors are influenced by both environmental exposures and genetic background and the heritability of these risk factors can be as high as 77%, 3 making it difficult to clearly separate CVD risk factors into genetic and nongenetic categories. The INTERHEART study has evaluated the effect of both physical and psychosocial factors on the risk of myocardial infarction and has shown that a higher prevalence of psychological stress and other psychosocial factors like depression account for 34% of the population attributable risk for myocardial infarction, independently of physical risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…10 The interaction between these factors in the disease development can be mediated by epigenetic modifications. Epigenetic markers might explain the link between lifestyle and the risk of disease and have been proposed to be sensitive biomarkers and potential therapeutic targets for disease management.…”
Section: Introductionmentioning
confidence: 99%
“…If closer relatives resemble each other more for metabolic syndrome traits than more distant relatives do, this indicates that familial factors, including genetic factors and familyshared environmental infl uences, are important for these traits. The heritability estimates observed in these studies vary widely, with heritability ranging 24-90% for BMI ( 18,(21)(22)(23)(24), 10-75% for fasting glucose ( 17,20,(22)(23)(24)(25), 20-55% for fasting insulin ( 17,20,22,23,26 ), 0.03-72% for triglycerides ( 17,19,20,(22)(23)(24)(25)27 ), 25-98% for LDLcholesterol ( 17,19,20,22,23,27 ), 30-80% for HDL cholesterol ( 17,19,20,22,24,25,27 ), 30-74% for total cholesterol ( 17,19,20,(22)(23)(24)27 ), 20-71% for SBP ( 14,17,…”
mentioning
confidence: 99%